2020
DOI: 10.1186/s12913-020-05898-9
|View full text |Cite
|
Sign up to set email alerts
|

Design of a care pathway for pharmacy-based PrEP delivery in Kenya: results from a collaborative stakeholder consultation

Abstract: Introduction In Kenya, pre-exposure prophylaxis (PrEP) for HIV prevention is almost exclusively delivered at HIV clinics. Developing novel PrEP delivery models is important for increasing the reach of PrEP. Delivery of PrEP through pharmacies is one approach utilized in the US to improve accessibility. Retail pharmacies are commonly used as a first-line access point for medical care in Kenya, but have not been utilized for PrEP delivery. We conducted a collaborative consultative meeting of stakeholders to deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
69
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 39 publications
(72 citation statements)
references
References 21 publications
3
69
0
Order By: Relevance
“…186 A recent stakeholder consultation in Kenya showed that providers and implementers were strongly supportive of developing and testing a model for pharmacy-based oral PrEP delivery to increase oral PrEP access. 187 The consultative group developed a pathway for pilot testing pharmacy-based oral PrEP delivery in Kenya. Expanding PrEP delivery beyond health clinics and aligning FP and HIV prevention delivery channels has the potential to increase uptake of both PrEP and contraception, and respond to women's desire for convenient and less stigmatized services.…”
Section: Discussionmentioning
confidence: 99%
“…186 A recent stakeholder consultation in Kenya showed that providers and implementers were strongly supportive of developing and testing a model for pharmacy-based oral PrEP delivery to increase oral PrEP access. 187 The consultative group developed a pathway for pilot testing pharmacy-based oral PrEP delivery in Kenya. Expanding PrEP delivery beyond health clinics and aligning FP and HIV prevention delivery channels has the potential to increase uptake of both PrEP and contraception, and respond to women's desire for convenient and less stigmatized services.…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence points to a decline in the utilisation of inpatient and outpatient services in Kenya [15]; pharmacies could be absorbing some of this patient traffic. Pharmacies in Kenya have been involved in the delivery of several health interventions, such as malaria rapid testing, HIV self-testing, and other disease screening services [16][17][18][19][20]. Consequently, private retail pharmacies can be used to deliver COVID-19 rapid testing services, hence expanding testing coverage and access to affordable and timely testing.…”
Section: Rapid Diagnostic Tests (Rdtsmentioning
confidence: 99%
“…We will begin by identifying potential attributes and levels from preliminary qualitative data and the literature. 22 We will conduct up to five focus group discussions (FGDs) with women (n=5-10) and five FGDs with health providers (n=5-10 community health workers and nurses), and five semi-structured interviews with decision-makers to further refine and identify additional attributes. We primarily want to assess whether women would consider going to a pharmacy instead of an antenatal care clinic during pregnancy for HIV prevention products or services.…”
Section: Selection Of Attributes and Levelsmentioning
confidence: 99%
“…We will leverage ongoing studies to identify potential community pharmacies for inclusion in the study. 22 Study design and data collection Qualitative data will be collected through individual interviews using an interview guide based on TDF constructs. As ascertained in prior studies, we will assess select constructs from the TDF based on their likely influence on implementation.…”
Section: Study Setting and Populationmentioning
confidence: 99%
See 1 more Smart Citation